2006
DOI: 10.1016/j.jhin.2005.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of rooms, medical equipment and ambulances using an aerosol of hydrogen peroxide disinfectant

Abstract: A programmable device (Sterinis, Gloster Sante Europe) providing a dry fume of 5% hydrogen peroxide (H(2)O(2)) disinfectant was tested for decontamination of rooms, ambulances and different types of medical equipment. Pre-set concentrations were used according to the volumes of the rooms and garages. Three cycles were performed with increasing contact times. Repetitive experiments were performed using Bacillus atrophaeus (formerly Bacillus subtilis) Raven 1162282 spores to control the effect of decontamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
110
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(114 citation statements)
references
References 6 publications
2
110
0
2
Order By: Relevance
“…Moreover, hydrogen peroxide fumigation does not appear to damage materials or sensitive equipment (French et al, 2004;Rogers et al, 2005). Therefore, hydrogen peroxide fumigation has been used for decontaminating laboratories and laboratory equipment (Klapes & Vesley, 1990;Kahnert et al, 2005;Hall et al, 2007), medically-implanted wires (Fichet et al, 2004) and medical equipment (Andersen et al, 2006), hospital rooms (French et al, 2004), biological safety cabinets (Hillman, 2004), and animal holding rooms (Krause et al, 2001). The present study demonstrates that F. tularensis Schu S4 is inactivated on various material surfaces when exposed to VHP fumigation in a BSC III.…”
Section: Figurementioning
confidence: 99%
“…Moreover, hydrogen peroxide fumigation does not appear to damage materials or sensitive equipment (French et al, 2004;Rogers et al, 2005). Therefore, hydrogen peroxide fumigation has been used for decontaminating laboratories and laboratory equipment (Klapes & Vesley, 1990;Kahnert et al, 2005;Hall et al, 2007), medically-implanted wires (Fichet et al, 2004) and medical equipment (Andersen et al, 2006), hospital rooms (French et al, 2004), biological safety cabinets (Hillman, 2004), and animal holding rooms (Krause et al, 2001). The present study demonstrates that F. tularensis Schu S4 is inactivated on various material surfaces when exposed to VHP fumigation in a BSC III.…”
Section: Figurementioning
confidence: 99%
“…Some researchers have pointed out that microorganisms on the patient's cabin and medical equipment surfaces could become a serious source of infection transmission (Andersen et al 2006;Kanz 1981;Nigam and Cutter 2003a). One study indicated that 13 out of 105 swab samples (12.4%) which were taken from different area of the ambulances were positive for MRSA (Kanz 1981).…”
Section: Decontamination Practicesmentioning
confidence: 99%
“…), intervention in traumatic injuries, having to carry out a medical intervention in a confined space or a dark environment, and limited time for decontamination of the contaminated medical equipment and patient's cabin (Becker et al 2003;Boal, Hales, and Ross 2005; Gershon et al 1985;Hochreiter and Barton 1988;Merchant et al 2009;Pepe et al 1986;Reed et al 1993;Valenzuela et al 1985). Some researchers have pointed out that microorganisms in the patient's cabin and on the surfaces of the medical equipment could become a serious source of infection transmission (Andersen et al 2006;Kanz 1981;Nigam and Cutter 2003a). In additionally, the presence of multiple drug resistant (MDR) pathogens including methicillin-resistant Staphylococcus spp., Stenotrophomonas maltophilia, Pseudomonas spp., Klebsiella spp.…”
mentioning
confidence: 99%
“…It can be used in two methods: vaporized hydrogen peroxide (VHP) when the compound remains in the vapor phase, and hydrogen peroxide vapor (HPV) when a very small amount of condensation is induced deliberately (Gale et al, 2009) after 120 minutes (Andersen et al, 2006). A VHP system was tested on a non-flying C-141 cargo aircraft, showing an inactivation rate of 99.9% after 120 hours (McVey, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…During the 2001 anthrax attacks, chlorine dioxide, vaporized hydrogen peroxide, paraformaldehyde, methyl bromide, and ethylene oxide were approved for use (Kempter, 2005). Hydrogen peroxide in the vapor phase was used with a high degree of success during the 2001 attacks (McVey, 2005) and tests in both the laboratory (Andersen et al, 2006;Oh et al, 2005) and field studies on grounded aircraft (Gale et al, 2008) have shown its efficacy. This method cannot be used on airworthy aircraft because it has detrimental material impacts (Gale et al, 2009;Verce et al, 2008).…”
Section: Introductionmentioning
confidence: 99%